Penerapan Data Mining Prediksi Jumlah Wisatawan Menggunakan Algoritma Regresi Linear Berganda - dikesuma, hendra; Yanto, Robi; Alfiarini, Alfiarini; Ahmadi, Ahmadi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Lubuklinggau is known as a transit city which is located directly on the border with 2 provinces, namely Bengkulu and Jambi. The city of Lubuklinggau has a tourism program known as "Let's ngelong Lubuklinggau, where the number of tourist attractions, both natural and artificial, continues to increase. Currently, visiting tourists continue to increase, where in 2010 it was 8,449 people and in 2022 it was 17,932 people. As tourist attractions increase, it is necessary to increase adequate accommodation facilities. The increase in the number of tourists, which is not accompanied by an increase in accommodation facilities, has resulted in a decrease in the number of tourists visiting. So it is necessary to analyze the number of tourists visiting to improve service facilities for tourists, especially the provision of accommodation. By predicting the number of tourists, it will help the Lubuklinggau City government to carry out strategies in an effort to fulfill the accommodation needed by tourists in an effort to increase the number of tourists. The multiple linear regression method can be used to predict the number of tourists. This is proven by the predicted results of the number of tourists in 2025 being 25,495 people, which is influenced by the determination value of the availability of rooms and hotel guests of 82.6% and the positive influence variable is very strong with a value of 0.908 on the number of tourists